2004
DOI: 10.1038/oby.2004.59
|View full text |Cite
|
Sign up to set email alerts
|

Hyperadiponectinemia in Newborns: Relationship with Leptin Levels and Birth Weight

Abstract: PARDO, INÊ S M.C.G., BRUNO GELONEZE, MARCOSA TAMBASCIA, AND ANTONIO A BARROS-FILHO. Hyperadiponectinemia in newborns: relationship with leptin levels and birth weight. Obes Res. 2004;12:521-524. Objective: Adiponectin is the only adipose-specific hormone that, despite its exclusive production by adipose tissue, is reduced in obesity and is inversely correlated with leptin levels in adults. The aim of this study was to evaluate the adiponectin concentration in umbilical cord blood at different gestational ages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
40
3
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 22 publications
11
40
3
1
Order By: Relevance
“…Previous studies have revealed conflicting results: some (25,28,29,31) found a positive association between ponderal index and adiopnectin, whereas others (20,30) showed no such relation. Hormonal factors, stress or gestational age may be responsible for the reported conflicting data (20, 25, 27 -31) but no previous study has performed multivariate adjustment to control for the potential effect of these potential confounders.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Previous studies have revealed conflicting results: some (25,28,29,31) found a positive association between ponderal index and adiopnectin, whereas others (20,30) showed no such relation. Hormonal factors, stress or gestational age may be responsible for the reported conflicting data (20, 25, 27 -31) but no previous study has performed multivariate adjustment to control for the potential effect of these potential confounders.…”
Section: Discussionmentioning
confidence: 85%
“…The strengths of this study include its relatively large size, which has provided the power needed to allow statistical documentation of important associations, the blinded measurements of hormone levels that minimizes misclassification, and the fact that this is the first study to perform multivariable adjustment for potential confounders such as gestational age, maternal factors and stress (28). While all previous studies have utilized cord blood, this research studied the above association using serum adiponectin levels of neonates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to regulating body metabolism, adiponectin is also produced within the intrauterine environment (52,(103)(104)(105). The findings that adiponectin is present in cord blood (103), positively correlates with birth weight (52,104), and is highly produced by both the placenta and the fetus (52,105) suggest that this adipocytokine may play a key role in fetal growth, probably enhancing the growth-promoting effect of insulin through its insulin-sensitizing action (52).…”
Section: Adiponectin In Iugrmentioning
confidence: 97%
“…7 In contrast, in full-term neonates, during the first few days of life, serum or plasma adiponectin levels correlate positively with size at birth, neonatal adiposity and circulating levels of leptin. [8][9][10][11][12][13][14] It has been suggested that the factors implicated in adiponectin inhibition, which are mainly related to the amount/distribution of body fat, are not operative in newborns. 9 It has also been proposed that adiponectin has a role in fetal growth and development.…”
mentioning
confidence: 99%